2017
DOI: 10.1002/sdtp.11954
|View full text |Cite
|
Sign up to set email alerts
|

P‐105: Sensor‐based Latency Reduction Method for Virtual Reality Head Mounted Display

Abstract: This paper proposes a low computational complexity-based prediction method that can effectively remove the motion-to- photon latency in a HMD. The proposed method combined the advantages of the linear extrapolation and sensor-based extrapolation, and hence, it had high accuracy and low computational complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Therefore, minimizing the time delay or, at least, keeping the size of the time lag consistent might be critical to reduce the VR sickness. Recently, Seo et al (2017) suggested a sensor-based prediction method to reduce the motion-to-photon latency in an HMD.…”
Section: Latencymentioning
confidence: 99%
“…Therefore, minimizing the time delay or, at least, keeping the size of the time lag consistent might be critical to reduce the VR sickness. Recently, Seo et al (2017) suggested a sensor-based prediction method to reduce the motion-to-photon latency in an HMD.…”
Section: Latencymentioning
confidence: 99%
“…Traditional EKF-and UKF-based algorithms [45], [46] can correct orientation prediction using only accelerometer readings. However, a greater amount of yaw information of orientations can be obtained from magnetometer readings.…”
Section: A Overviewmentioning
confidence: 99%